Hormone Biotechnology - Maitra, Saumen Kumar (Daya Publishing, 2007)
Papers presented at the Symposium on Reproductive Biology and Comparative Endocrinology, held at Santiniketan in February 2005; Samir Bhattacharya, b. 1942, Indian zoologist.